The Organizational Model of the Judicial Management Office in the Judicial Power of Santa Fe Province - Drago, Mariana Jimena (Ediciones UNL. Secretaría de Extensión de la UNL, 2019)
Administrative design and reorganization policies include deliberations on organizational forms. Furthermore, these policies involve struggles related to the symbols, legitimacy and identity of the public administration. A public administration theory must account for the complexity of the administrative organization, its actors and the change that takes place in it. The purpose of the present work is to conduct an organizational study applied to the Office of Judicial Management belonging to the Judicial Power of Santa Fe Province. Moreover, a global organizational proposal will be made. The fundamental conceptual areas of any public organization will be considered: socio-technical field, political-cultural field and control and improvement field. Finally, the technique of Strategic Orientation Models (SOMs) will be applied to the Judicial Management Office, displaying different potential scenarios of change.